Dengue haemorrhagic fever presenting with cholestatic hepatitis: two case reports and a review of literature - Yudhishdran, Jevon (BioMed Central, 2014)
BACKGROUND: Dengue fever is a common mosquito borne viral fever in South Asia, which causes significant morbidity and mortality. Dengue fever is well known to involve the liver, especially in dengue hemorrhagic fever. The hepatic involvement is usually that of a mild hepatitis with transaminase derangement without jaundice. In cases of dengue hemorrhagic fever where shock has ensued, a severe hepatitis with gross derangements of transaminases and bilirubin may occur. These are two rare cases of adult patients with dengue hemorrhagic fever presenting with a cholestatic type of jaundice. CASE PRESENTATION: This case report describes two female patients aged 30 and 46 years who presented with fever, icterus and biochemical analysis revealed cholestatic jaundice. Evolution of the clinical picture and dropping platelets prompted serological investigations in the form of dengue non-structural protein 1 antigen and dengue immunoglobulin M which confirmed acute dengue infection. CONCLUSION: These cases highlight the importance of considering dengue fever as a differential diagnosis even in the presence of a cholestatic jaundice, especially in countries where dengue fever is endemic, and in travelers returning from dengue endemic countries. The early diagnosis of dengue fever and timely institution of supportive fluid management is essential to prevent morbidity and mortality.